2016
DOI: 10.1159/000448663
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities in Dental Caries among Six-Year-Old Children in the Netherlands

Abstract: The aim of this study was to investigate potential differences in caries prevalence of children from ethnic minority groups compared to native Dutch children and the influence of socio-economic status (SES) and parent-reported oral health behaviour on this association. The study had a cross-sectional design, embedded in a population-based prospective multi-ethnic cohort study. 4,306 children with information on caries experience, belonging to 7 different ethnic groups, participated in this study. The decayed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 33 publications
6
33
0
Order By: Relevance
“…A similar result was also reported in northern Europe (the Netherlands) by van der Tas et al [3,7] that observed a similar result in a greater sample than the present one.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A similar result was also reported in northern Europe (the Netherlands) by van der Tas et al [3,7] that observed a similar result in a greater sample than the present one.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies enlightened a gap between Italy and other EU countries, where there is a screening program across the population (infantile, adolescent, and adult) at regular intervals of ten years, which allowed, from 1973, to reduce drastically the prevalence of caries, especially in preschool age [27][28][29]. On the contrary, the preschool caries risk pattern in Italy appears to be similar to that reported by van der Tas et al [3] and the caries-free participants percentage even higher in Italy (81.6% vs 77.1%). is is still far from what was asked by the World Health Organization (WHO) targets for 2010, which were to provide for a reduction of caries, with an average of caries-free participants equal to approximately 90% among preschool children [30].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies are needed in which more confounders are controlled for to determine how parents' WTI is affected by ethnicity, education level, income, and other cultural and sociodemographic factors. From the literature, it is known that children from lower educated parents and immigrants have a higher risk of dental caries compared to children from higher educated parents and Western background (25,26). An interesting research question to investigate is whether parents' WTI in their children's oral health plays an intermediating role in the explanation of socioeconomic and ethnic inequalities in children's dental caries experience.…”
Section: Willingness To Invest In Children's Oral Healthmentioning
confidence: 99%